Impact of Interim Methadone Maintenance on HIV Risk Behaviors - Wilson, Monique E. (Springer US, 2010)
The extent to which interim methadone (IM) without counseling reduces HIV risk behavior has not been reported. The AIDS Risk Assessment scale was administered at baseline and 4-month follow-up to 319 adult heroin-dependent participants randomly assigned to IM or waiting list. On an intent-to-treat basis, there was a significantly greater reduction in drug injection and unprotected sex while high from baseline to follow-up, favoring the IM condition. Remedying the shortage of methadone capacity through the expansion of IM would be a worthwhile approach to reducing the spread of HIV infection.